Podjetniška demografija in značilnosti digitalizacije malih in srednje velikih podjetij: Slovenski podjetniški observatorij 2021 (University of Maribor Press, 2022)
Slovenian Enterprises and the Characteristics of Digitalization of Small and Medium Sized Companies: Slovenian Entrepreneurship Observatory 2021. In the first part of the monograph we focused on the business demography of Slovenian companies and compared it with the European one. The aim of this research is to obtain a basic insight into Slovenian companies and to understand how they are positioned in Europe. We analyzed the main characteristics of Slovenian companies and sole proprietors who were engaged in entrepreneurial activities in 2020. In the second part of the research, we examined the characteristics of digitalization from the business perspective. We focused primarily on the aspect of small and medium-sized enterprises, as they require the most support and incentives for the successful implementation of digitization. First, we provided an overview of the characteristics of the digitization process, its impact on companies and the characteristics of digital strategies and strategic support for digitization at the level of the EU and Slovenia, as well as an overview of Slovenia’s ranking on various scales for measuring digitization. We then analyzed the results of the survey we conducted among Slovenian companies and the supportive environment for entrepreneurship.